High-throughput screening for superhard carbon and boron nitride allotropes with superior stiffness and strength. (October 2018) - Zhang, Shihao; Legut, Dominik; Fu, Zhongheng; Germann, Timothy C.; Zhang, Ruifeng
Abstract: In search of intrinsically superhard materials with superior stiffness and strength, we performed a comprehensive high-throughput hunting on hundreds of carbon and BN allotropes based on energetic and mechanical criteria. Our results suggest that at ambient pressure, an approximate linear relationship exists between the ideal strengths and elastic moduli in two allotrope regions with high elastic moduli, while no carbon (BN) allotrope can possess both superior stiffness and strength than diamond (c-BN). With further consideration of pressure induced stiffening and strengthening, it is interestingly found that the strength enhancement shows distinct characteristic trend, resulting in some intriguing ultra-stiffening and strengthening phenomena. In particular, a superdense carbon allotrope termed as tI12-C was unexpectedly discovered to possess superior stiffness and strength than diamond under high pressure. Electronic structure analysis indicates that an increasing charge accumulation appearing in tI12-C under pressure is responsible for its ultra-stiffening and strengthening phenomena, differing from the appearance of abnormal charge depletions and the accompanied metallization in diamond under applied strain. These findings provide a fundamental basis for screening the novel superhard carbon and BN allotropes based on mechanical criteria, and highlight the importance to understand the effect of strain tunable electronic structure on mechanical response of materials. Graphical abstract: Image 1